PENGARUH PEMBERIAN PROBIOTIK EM-4 (EFFECTIVE MICROORGANISM-4) PADA PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN LELE SANGKURIANG (Clarias gariepinus) The Influence of EM-4 (Effective Microorganism-4) in Feed to the Growth and the Survival - Dwy Murphy Banjarnahor; Syammaun Usman; Rusdi Leidonald (AQUACOASTMARINE, 2016)
In the cultivation of fish consumption, the most important factors are the growth and survival. Catfish is a freshwater fish consumption that growth relatifely fast. This study was aimed to know the influence of EM-4 in feed to the growth and survival rate of catfish and to determine the amount of EM-4 effective concentration to the growth and survival rate of catfish (Clarias gariepinus). Fish fed 5 % of fish body weight per day. Feeding frequency of three times a day at 08.00 WIB, 13.00 WIB and 18.00 WIB. This study used a completely randomized design with 4 treatments : K (control), P1 (2ml/kg), P2 (4 ml/kg), P3 (6 ml/kg) with three replications. The result was tested by ANOVA, the results showed that concentration EM-4 on feed significantly affect the survival and weight of catfish, but did not significantly affect the fish length. Best weight growth rate was in P3 treatment and the best survival rate was in P2 treatment.Key words : Clarias gariepinus, EM-4, growth, survival rate